Degradasi Lahan dan Implikasinya terhadap Rencana Pola Ruang di Daerah Dataran Tinggi - Hiranya Rengganis; Iwan Rudiarto (Teknik PWK (Perencanaan Wilayah Kota), 2021)
Land degradation is a phenomena of the decreasing in land use function, potential use and irreplaceable organism. Many causes result in land degradation such as soil erosion, rain erosion which are all accelerated by human activities example agricultural activity. Increased agricultural activity is caused by an increase in population and also increasing food needs. Land exploitation for agricultural activities result in land degradation such as planting on conservation areas that cause erosion. Kledung Sub-district is one of the regions that practices massive agricultural land use and plants in a conservation land. Practices in Kledung Sub-district have caused floods and soil erosion in Kledung Sub-district in the last few years. The purpose of this study was to determine the level of land degradation that occurred in Kledung Sub-district and its implications for the land use planning to increase awareness of various parties about the dangers of land degradation. This research was conducted primarily by observation and secondary b examining documents about the indicators causing land degradation and conducting descriptive and quantitative analyzes. The quantitative analyze is using RUSLE (Revised Universal Soil Loss Equation). The analysis shows that the majority of erosion according to the Ministry of Forestry is moderate (>60-80 tons/ha/yr) covering1.231,01 Ha and according to Hammer which is very high (>100 tons/ha/yr) covering 469,62 Ha or 12,7% of the total area of Kledung Sub-district with a high level of erosion hazard it is necessary to evaluate the land use planning of Kledung Sub-district so that it can adjust the land use planning and the erosion hazard level in Kledung Sub-district.